Comparing the effectiveness of Transcranial direct current stimulation (tDCS) and mindfulness on working memory and clinical symptoms of adults with attention-deficit/hyperactivity disorder (ADHD): tDCS and mindfulness on ADHD - Mikaieli, Niloofar; Narimani, Mohammad; Hossein-Khanzadeh, Abbasali; Moradi-Kelarde, Sara (Chronic Diseases Journal, 2025)
BACKGROUND: Attention deficit/hyperactivity disorder (ADHD) is one of the most adverse neurological disorders that is associated with multiple defects in cognitive and behavioral dimensions and sometimes continues until adulthood. Due to the side effects of drug therapy, non-drug treatments have been welcomed for this disorder. The purpose of this study was to compare the effects of mindfulness-based cognitive therapy (MBCT) and transcranial direct current stimulation (tDCS) on working memory and clinical symptoms of adults with ADHD. METHODS: This experimental study had a multi-group pretest/posttest design in which an experimental group was exposed to tDCS (5 sessions of 20-minute interventions of electrical stimulation with the flow of 1 mA) and one other experimental group was exposed to MBCT (8 sessions of 90 minutes, three days a week), and the control group did not receive any intervention. Participants in this study were 45 male subjects (15 in each group), which were selected by the convenience method and online recall in social media groups. RESULTS: The mindfulness and electrical stimulation of the dorsolateral prefrontal cortex (DLPFC) had a significant effect on working memory and clinical symptoms of adults with ADHD. CONCLUSION: Based on the findings of this study, it is recommended that these methods be used by clinicians and practitioners in neurological clinics and psychological services as a method of intervention and prevention.